Layout Design Based on Capacity Planning at Mika MSMEs Using BOL Approach and BLOCPLAN Algorithm - Tantya Dega Wahyu Maharani; Dida Diah Damajanti; Murni Dwi Astuti (MOTIVECTION : Journal of Mechanical, Electrical and Industrial Engineering, 2023)
Based on historical data in 2020, Mika MSMEs could not meet the demand for gamis cloth production. It is proven that there is a capacity shortage that occurs in the third process, namely the sewing process as much, as 0.5%. The RCCP method with the BOL methodology was used to perform the capacity calculation, and the results suggested the necessity for an alternate addition of three workers to the sewing process. With an alternative usage fee of IDR 7,700,000/month and a profit of IDR 262,300,000/month. PAM tools help analyze the problem that there is transportation waste, with the largest percentage of 39.68% in Mika MSMEs. Layout improvements were made using the BLOCPLAN algorithm by considering the largest R-Score value. The proposed layout design provides for a displacement of 2080 meters/day, a transfer time of 1934 seconds/day, and the use of one production floor. Berdasarkan data historis pada tahun 2020, UMKM Mika tidak dapat memenuhi permintaan produksi baju gamis. Hal ini dibuktikan bahwa adanya kekurangan kapasitas yang terjadi pada proses ketiga yaitu proses sewing sebanyak 0.5%. Dilakukan perhitungan kapasitas menggunakan metode RCCP dengan pendekatan BOL, dan diperoleh usulan berupa perlunya alternative penambahan tiga tenaga kerja pada proses sewing. Dengan biaya penggunaan alternatif Rp7,700,000/bulan dan keuntungan sebesar Rp262,300,000/bulan. Tools PAM membantu melakukan analisis permasalahan bahwa terdapat pemborosan transportasi dengan persentase terbesar 39.68% di UMKM Mika. Dilakukan perbaikan tata letak menggunakan algoritma BLOCPLAN dengan memperhatikan nilai R-Score terbesar. Didapatkan usulan perancangan tata letak berupa perpindahan sebanyak 2080 meter/hari, waktu transportasi sebanyak 1934 detik/hari, dan dengan penggunaan satu lantai produksi.